Cocaine mutagenicity and hepatocarcinogenicity evaluations in rodents - Salvadori, Daisy Maria Favero [UNESP]; Barbisan, Luis Fernando [UNESP]; Bazo, A. P.; de Santana, E. Q.; Denadai, R.; de Oliveira, S. V.; Ribeiro, Lúcia Regina [UNESP]; de Camargo, JLV (Wiley-Blackwell, 1998)
The mutagenicity (clastogenicity) and the carcinogenicity (promoting potential) of cocaine were evaluated, respectively, by the mouse bone marrow micronucleus test (study I) and by the initiated rat liver bioassay (study II). In study I, two administration routes (i.p. and i.v.) and two sampling times (24 and 48 hours) after cocaine treatment were studied. Swiss male mice were treated with cocaine at doses of 0, 18, 37, and 75 mg/kg and 0, 2, 4, and 8 mg/kg by i.p. and i.v. routes, respectively. No significant differences were observed between treated and negative control groups regarding the frequencies of micronuclei and the polichromatic/normochromatic erythrocyte (PCE/NCE) ratios. In study II, the development of putative preneoplastic foci of hepatocytes expressing the enzyme glutathione S-transferase placental form (GST-P+) was utilized as the end-point marker in a 8-week rat liver bioassay. The animals were initiated for carcinogenesis by a single i.p. sub-carcinogenic dose of diethylnitrosamine (DEN). After a 6-week exposure to 5 or 10 mg/kg of cocaine i.v. twice a week there was no enhancement of GST-P+ foci development above the values of the control DEN-only treated animals. Also, cocaine did not induce any toxicity as evidenced by the absence of alterations of rat body and liver weights and of liver biochemical function and morphology. The results suggest that cocaine does not have a mutagenic effect on the mouse bone marrow cells or promoting activity on the rat hepatocarcinogenesis process. Teratogenesis Carcinog. Mutagen. 18:199-208, 1998. (C) 1998 Wiley-Liss, Inc.
Keywords: cocaine; micronucleus test; mouse bone marrow; rat liver carcinogenesis bioassay